In Vitro and In Vivo Evaluation of Chaetoceros sp. Immunomodulatory Effects in Red Hybrid Tilapia, Oreochromis spp. - Cheong, Hui Ann; Christianus, Annie; de Cruz, Clement Roy; Low, Chen Fei; Lee, Po Tsang; Abdullah, Maha; Md Yusoff, Fatimah; Shaari, Khozirah; Ismail, Intan Safinar; Ng, Grrace Hui Suan; Chong, Chou Min (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Diatoms are recognized as a valuable source of bioactive compounds that can stimulate the immune defense mechanisms of fish. This study aimed to assess the effects of Chaetoceros sp. in modulating the specific and non-specific immunity of red hybrid tilapia through in vitro functional assays, an in vivo feeding trial, and a bacterial challenge. The in vitro experiment (Phase One) examined the immune response of tilapia cells exposed to Chaetoceros sp. extract, while the in vivo experiment (Phase Two) evaluated the immune response following an 8-week dietary supplementation with Chaetoceros sp. powder. In Phase One, an 8 mg/mL concentration of Chaetoceros sp. extract demonstrated an overall enhancement in lysozyme activity and lymphocyte proliferation. In Phase Two, tilapia fed a diet containing 2% Chaetoceros sp. showed significantly improved lysozyme activity, while the 5% supplemented group exhibited a significant increase in lymphoproliferation activity (p < 0.05). Growth performance parameters were generally comparable among dietary groups, indicating that supplementation did not adversely affect growth. Notably, the 2% diet also enhanced fish survivability following a challenge with Streptococcus agalactiae. These findings highlight the immunomodulatory potential of the diatom Chaetoceros sp. as a functional feed additive for freshwater fish, particularly red hybrid tilapia, and suggest its positive impact on fish health management in aquaculture.